FAKTOR YANG MEMPENGARUHI PELANGGARAN DISIPLIN SISWA DAN IMPLIKASINYA TERHADAP LAYANAN BIMBINGAN DAN KONSELING - Ridho Ilahi; Syahniar Syahniar; Indra Ibrahim (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
Student’s discipline violation at SMA N X Padang are affected by internal and external  factors.  Findings  in  the  field  showed  that  many  students  broke  the  school’s discipline.  This research  is aimed to describe  internal  and external  factors  that  affected students’ discipline violation and those implications for Counseling and Guidance services. This  research  is  classified  into  quantitative  research  in  descriptive  type.  The  research subjects are 130 students who violate the discipline at SMA N X Padang. The research instrument  is questionnaire.  The findings  of the research revealed:  internal and external factors which affected violation of discipline is at medium category.